2011
DOI: 10.4103/2229-5178.79867
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous hamartoma of infancy

Abstract: Fibrous hamartoma of infancy (FHI) is a rare, benign tumor of the subcutis and lower dermis, which usually occurs within the first 2 years of life. Ninety one percent of the tumors occur in the first year of life. The histogenesis of FHI is unclear. The clinical course is typically benign and prognosis excellent. The physical characteristics of the subcutaneous mass in a child may suggest a malignant process; however, FHI should be included in the differential diagnosis. The prognosis of FHI is excellent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…33 The differential diagnosis for subcutaneous swelling in an infant includes both benign and malignant soft tissue tumours such as epidermoid cyst, recurring digital fibrous tumour, juvenile aponeurotic fibroma, juvenile hyaline fibromatosis, palmoplantar fibromatosis, histiocytoma, leiomyosarcoma, fibrosarcoma. 27,37 In our study we reported total 20 hamartoma cases, out of which patient with intestinal hamartoma died due to cardiopulmonary arrest. Laryngeal hamartoma patient presented with stridor which is near to fatal.…”
Section: Discussionmentioning
confidence: 83%
“…33 The differential diagnosis for subcutaneous swelling in an infant includes both benign and malignant soft tissue tumours such as epidermoid cyst, recurring digital fibrous tumour, juvenile aponeurotic fibroma, juvenile hyaline fibromatosis, palmoplantar fibromatosis, histiocytoma, leiomyosarcoma, fibrosarcoma. 27,37 In our study we reported total 20 hamartoma cases, out of which patient with intestinal hamartoma died due to cardiopulmonary arrest. Laryngeal hamartoma patient presented with stridor which is near to fatal.…”
Section: Discussionmentioning
confidence: 83%
“…FHI is a soft tissue mass with a characteristic morphology including three histologic components: intersecting fascicles of dense fibrocollagenous tissue, loosely textured areas of immature basophilic or myxoid round or primitive mesenchymal cells, and mature adipose tissue ( 3 ). FHI is usually diagnosed before the age of 2 years and males are more commonly affected (2.4:1) ( 4 ). Most frequently, FHI presents as a solitary nontender soft tissue mass involving the axilla, upper arm, trunk, inguinal region, and chest wall.…”
Section: Discussionmentioning
confidence: 99%
“…FHI is most commonly found in axilla, shoulder, upper arm, inguinal region, and chest wall. Less common locations include head and neck, scrotum, legs, and foot [4].…”
Section: Discussionmentioning
confidence: 99%